Extreme intraocular pressure and steroid-dependent iritis. Issue 1 (January 2023) - Samuelson, Thomas W.; Huang, Marshall J.; Larsen, Christine L.; Sheybani, Arsham; Levin, Ariana; Ertel, Monica; Pantcheva, Mina; Panarelli, Joseph F.; Do, Anna
Abstract : A 50-year-old ophthalmic technician had chronic iritis and extreme IOP despite maximal medical therapy. Surgical intervention provided excellent relief, despite a bumpy and precarious road to recovery. Abstract : A 50-year-old ophthalmic technician was referred by her retina specialist for urgent consultation due to markedly elevated intraocular pressure (IOP) unresponsive to medical therapy. Her history included chronic polyarticular juvenile rheumatoid arthritis and chronic uveitis requiring ongoing topical steroid therapy. She had a sub-Tenon injection of Kenalog (triamcinolone) 18 months prior to referral. Chronic topical anti-inflammatory therapy included nepafenac (Ilevro) and prednisolone acetate 2 times a day. Attempts to discontinue topical steroid resulted in worsening inflammation. The patient was referred when the IOP measured 44 mm Hg in the left eye despite aggressive medical therapy, including acetazolamide. The IOP improved slightly when loteprednol was substituted for prednisolone acetate. Current medications in the left eye include brimonidine 3 times a day, loteprednol 2 times a day, nepafenac 2 times a day, and fixed combination latanoprost + netarsudil at bedtime. Her only medication in the right eye was travoprost. She is intolerant to dorzolamide. She was also taking acetazolamide 500 mg 2 times a day. She was not taking any anticoagulants. Past surgical history included cataract surgery in each eye. She has not had laser trabeculoplasty in either eye. Examination revealed uncorrected visual acuity of J1+ in the right eye (near) and 20/30 in the left eye (mini-monovision). There was no afferent pupillary defect. There was mild band keratopathy in each eye while the central cornea was clear in both eyes without keratic precipitates. Here angles were open to gonioscopy without peripheral anterior synechia. There was mild to moderate flare in each eye with trace cells. The IOP was 17 mm Hg in the right eye and 31 mm Hg in the left. Central corneal thickness measured 560 μm and 559 μm in the right and left eye respectively. There was a well-positioned intraocular lens within each capsule with a patent posterior capsulotomy. There was mild vitreous syneresis but no vitreous cell. The cup to disc ratio was 0.5 in each eye with a symmetrical neural rim. The retina was flat without macular edema. Visual field was normal in both eyes (Figures 1 and 2 ). Optical coherence tomography of retinal nerve fiber layer (RNFL) is shown in Figure 3 and retinal ganglion cell layer is shown in Supplemental Figure 1 (http://links.lww.com/JRS/A756 ). Please comment on your management of this patient's left eye.